LITERATURE REVIEW: PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI MASALAH BELAJAR SISWA - Yulianti Yulianti; Sinta Nurzulina Putri; Nuramita Nuramita; Nurul Husna (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This article contains the role of guidance and counseling teachers in overcoming student learning problems. In this article the author explains starting from the meaning of learning, understanding learning problems and forms of learning problems, what factors cause children to experience learning problems and also what is the role of guidance and counseling teachers in overcoming them. This article was created using the library study method, namely where the reference sources for this article come from reading sources such as articles and books related to the title that has been taken. The role of guidance and counseling teachers is very necessary in overcoming student learning problems, but it is not only guidance and counseling teachers but it is also the responsibility of teachers and school leaders.